The anthropology of law - Pirie, Fernanda (Oxford, United Kingdom : Oxford University Press, 2013)
1. Introduction 2. Order, Disputes, and Legal Pluralism 3. Legal Thought: Meaning and Form 4. Law as an Intellectual Tradition 5. Idealism, Tradition, and Authority 6. Legalism 7. Morality and Community 8. Law and the State 9. Conclusion.
Includes bibliographical references (pages 231-255) and index.
Keywords: Law and anthropology